Switching on the Big Burn of 2017 - Balch, Jennifer K.; Schoennagel, Tania; Williams, A. Park; Abatzoglou, John T.; Cattau, Megan E.; Mietkiewicz, Nathan P.; St. Denis, Lise A. (Fire (Basel, Switzerland), 2018)
Fuel, aridity, and ignition switches were all on in 2017, making it one of the largest and costliest wildfire years in the United States (U.S.) since national reporting began. Anthropogenic climate change helped flip on some of these switches rapidly in 2017, and kept them on for longer than usual. Anthropogenic changes to the fire environment will increase the likelihood of such record wildfire years in the coming decades. The 2017 wildfires in the U.S. constitute part of a shifting baseline in risks and costs; meanwhile, effective policies have lagged behind, leaving communities highly vulnerable. Policy efforts to build better and burn better, in the U.S. as well as in other nations with flammable ecosystems, will promote adaptation to increasing wildfire in a warming world.